Severe Spontaneous Echo Contrast/Auricolar Thrombosis in "Nonvalvular" AF: Value of Thromboembolic Risk Scores. Issue 1 (11th November 2016) - MASCIOLI, GIOSUÈ; LUCCA, ELENA; MICHELOTTI, FEDERICA; ALIOTO, GIUSY; SANTORO, FRANCO; BELLI, GUIDO; ROTA, CRISTINA; ORNAGO, OMBRETTA; SIRIANNI, GIOVANNI; PULCINI, EMANUELA; PENNESI, MATTEO; SAVASTA, CARLO; et al.
Abstract : Background: Patients with atrial fibrillation (AF) have an increased thromboembolic risk that can be estimated with risk scores and sometimes require oral anticoagulation therapy (OAT). Despite correct anticoagulation, some patients still develop left atrial spontaneous echo contrast (SEC) or thrombosis. The value of traditional risk scores (R2 CHADS2, CHADS2, and CHA2 DS2 ‐VASc) in predicting such events remains controversial. Methods and Results: The aim of our study was to explore variables linked to severe SEC or atrial thrombosis and evaluate the performance of traditional risk scores in identifying these patients. In order to do this, we retrospectively analyzed 568 patients with nonvalvular nonparoxysmal AF who underwent electrical cardioversion from January 2011 to December 2016 after OAT for a minimum of 4 weeks. A transesophageal echocardiogram was performed in 265 patients for various indications, and 24 exhibited left atrial SEC or thrombosis. Female gender, history of heart failure or left ventricular ejection fraction <40%, and high levels (>1 mg/dL) of C‐reactive protein (CRP) were independently associated with left atrial SEC/thrombosis. A score composed by these factors (denominated HIS [H eart Failure, I nflammation, and femaleS ex]) showed a sensitivity of 79% and a specificity of 60% (area under receiver operating characteristic curve 0.695, P = 0.002) in identifying patients with a positive transesophageal echo; traditional risk scores did not perform as well. Conclusions: In patients with persistent AF and suboptimal anticoagulation, a risk score composed by history of heart failure, high CRP, and female gender identifies patients at high risk of left atrial SEC/thrombosis when its value is >1.